Longitudinal changes in objectively measured physical activity, sedentary behavior and sleep in Spanish adolescents - Fernández-Argüelles, Daniel (2025)
Longitudinal evidence on the evolution of physical activity (PA), sedentary behavior and sleep in adolescents is still scarce, especially in Spanish contexts. Purpose: The present study aimed to assess the wakefulness movement and sleep progression from early to mid-adolescence with 24-hours accelerometry. Methodology: Participants included 229 adolescents (123 males, 106 females) aged 13 to 15 years (13.28 ± .57) from a city in the north of Spain. Three repeated measures were taken in 3 consecutive years. PA, sedentary behavior and sleep variables were measured using ActiGraph GT3x accelerometers over a full week. Anthropometric measures were taken to obtain BMI and socioeconomic status was assessed with a validated questionnaire. Statistical analyses included linear mixed models. Results: Data showed that sedentary behavior and vigorous PA increased over time, whereas light PA, moderate PA and energy expenditure decreased. Both total sleep time and sleep efficiency decreased, whereas sleep onset and offset were delayed. Conclusions: Over the 3-year period, adolescents worsened in most of the variables analyzed. These findings highlight the need to develop both PA and sleep interventions during adolescence.